PERBANDINGAN PENDAPATAN NELAYAN HAND LINE PERAHU BERCADIK DI NEGERI YAINUELO KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Asti Syafira Makatita; Johanis Hiariey; Yolanda MTN Apituley (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2020)
Inputs diversity among fishermen while catching can result in different number of cathes. The use of good inputs and efficient fishing gears leads to increasing of fishermen's income. This research was conducted during October 2019 on 15 hand-line fishermen in Yainuelo, Amahai District, Central Maluku Regency. The purpose of this study was to calculate the hand-line fishermen income and to compare the income among them. The results show that the average income of hand line boat fishermen in October 2019 was Rp. 3,444,357 and six of the fifteen fishermen get income above the average value, while the rest are below the average